2010
DOI: 10.1021/pr100680a
|View full text |Cite
|
Sign up to set email alerts
|

S-Alkylating Labeling Strategy for Site-Specific Identification of the S-Nitrosoproteome

Abstract: S-nitrosylation, a post-translational modification of cysteine residues induced by nitric oxide, mediates many physiological functions. Due to the labile nature of S-nitrosylation, detection by mass spectrometry (MS) is challenging. Here, we developed an S-alkylating labeling strategy using the irreversible biotinylation on S-nitrosocysteines for site-specific identification of the S-nitrosoproteome by LC-MS/MS. Using COS-7 cells without endogenous nitric oxide synthase, we demonstrated that the S-alkylating l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 99 publications
4
67
1
Order By: Relevance
“…We have previously shown by liquid chromatography-tandem mass spectrometry (LC-MS-MS) analyses that cysteine residues 300, 381, 439, 466, 520, and 619 of ␤-catenin are possible substrates for SNO by NO (26). In addition, Cys213 was identified as a potential SNO site in another proteomics study (28). To determine which cysteine residue of ␤-catenin the inhibitory effects of NO on the transcriptional activity of ␤-catenin are attributable to, we generated ␤-catenin mutants in which cysteine residues were replaced by nonnitrosylable serine.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We have previously shown by liquid chromatography-tandem mass spectrometry (LC-MS-MS) analyses that cysteine residues 300, 381, 439, 466, 520, and 619 of ␤-catenin are possible substrates for SNO by NO (26). In addition, Cys213 was identified as a potential SNO site in another proteomics study (28). To determine which cysteine residue of ␤-catenin the inhibitory effects of NO on the transcriptional activity of ␤-catenin are attributable to, we generated ␤-catenin mutants in which cysteine residues were replaced by nonnitrosylable serine.…”
Section: Resultsmentioning
confidence: 98%
“…We also identified other Cys residues on ␤-catenin that could be targets for SNO, namely, Cys300, -381, -439, -466, and -520 (26). Furthermore, Cys213 and -520 were identified as potential SNO sites in large-scale proteomics assays (27,28). In addition to its effects at cell-cell junctions, it has been shown that NO can inhibit the transcriptional activity of ␤-catenin in the nucleus and reduce proliferation of cancer cells (29,30).…”
mentioning
confidence: 87%
“…To more precisely identify S-nitrosylated proteins and their modified Cys residues, we used a site-specific proteomics approach to characterize S-nitrosylated peptides. In this method, the biotinylated proteins were first subjected to tryptic digestion before biotin-affinity purification, and the biotinylated peptides were then affinity purified for further analysis (Hao et al, 2006;Chen et al, 2010). Using this method, we analyzed and identified S-nitrosylated peptides from Col-0 and gsnor1-3 seedlings.…”
Section: Site-specific Identification Of S-nitrosylated Proteins In Cmentioning
confidence: 99%
“…Although the method is relatively simple, the number of S-nitrosylated proteins identified by shotgun proteomics is often few due to various technical limitations (Torta et al, 2008). The identification capacity of nitrosoproteomics was greatly improved by the site-specific strategy, in which biotinylated proteins were first digested by trypsin and the enriched peptides were then characterized by mass spectrometry (Hao et al, 2006;Chen et al, 2010). Moreover, S-nitrosylated Cys residues can also be identified from site-specific nitrosoproteomic analysis.…”
mentioning
confidence: 99%
“…Experimentally these algorism were found to be 75% accurate at predicting sites of S-nitrosation [56]. However, these motifs have been criticised due to the high concentrations of NO donor used in the founding experiments to map S-nitrosation sites [57,58], and so provide a platform for the prediction algorithm. Supra-physiological concentrations of NO may have resulted in the identification of motifs that lack biological significance.…”
Section: A Consensus Motif For Selective and Targeted Protein S-nitromentioning
confidence: 99%